Foreword to “Art music by Caribbean Composers” - Diaz Diaz, Edgardo (International Journal of Bahamian Studies, 2011)
The present volume of The International Journal of Bahamian Studies is the beginning of a long-needed project aimed at compiling and organizing the work by composers from the Caribbean.